Economic Valuation Of Green Open Space (Gos) And Biodiversity In Banda Aceh - Dharma, Wira (2021)
The ecological benefits of urban forests can be measured or calculated economically using multiple approaches. Therefore, the need to know the price that may be acquired if the benefits of urban forests are measured or calculated in monetary units so that the benefits of urban forest can be seen. This study aims to determine the change of green open space (GOS) land cover in urban forest, diversity of vegetation, birds, small mammals, the carbon stock and measure the Total Economic Value (TEV). Research data used in this study involves the pattern of land use changes by analysing satellite images taken in 2004 (before the tsunami), 2005 (after the tsunami), 2011, 2013 and 2016. Biological data was obtained through analysing the vegetation and animals. Total economic value of the natural resources was obtained by interviewing people who interact directly or indirectly with the study areas. TEV consists of use value and non-use value, where the direct use of urban forest in Banda Aceh is providing firewood and ecotourism. The form of indirect use is providing carbon value. Option value is in the form of benefits of biodiversity, and existence value is the existence of its flora and fauna. Forest cover in urban forest in Banda Aceh was reduced by 0.6 ha (1.3%) from 2004 to 2005. This was due to the great earthquake and tsunami disaster that struck the City of Banda Aceh in late 2004. However, in the course of time, the forest cover also continued to change and increase until 2016.